Crafting Presence : The American Essay and the Future of Writing Studies - Wallack, Nicole B. (Book collections on Project MUSE., 2016)
The author illuminates the most important quality of the essay as a literary form: the writer's 'presence'. This book demonstrates how accounting for presence provides a flexible and rigorous heuristic for reading that can help teach students not just writing skills, but writing practices.--description provided by publisher.